Efficacy comparison of cetirizine and loratadine for allergic rhinitis in children - Juliana, Juliana; Evalina, Rita; Irsa, Lily; Loebis, M. Sjabaroeddin (Paediatrica Indonesiana, 2012)
Background Allergic rhinitis represents a global health problem affecting 10% to more than 40% of the population worldwide. Several studies in recent years have described the efficacy of second-generation antihistamines in younger children. It is not well established whether cetirizine is more effective than loratadine in reducing symptoms of allergic rhinitis. Objective The objective of this study was to compare the efficacy of loratadine with cetirizine for treatment of allergic rhinitis. Methods We conducted a randomized, double-blind, controlled trial of 100 children, aged 13 to 16 years, from October to November 2009 at two junior high schools in Medan. Group I received 10 mg of cetirizine and group II received 10 mg of loratadine, each once daily in the morning for 14 days. Drug efficacy was assessed by changes from baseline symptom scores and evaluation of therapeutic responses after 3 days, 7 days and 14 days of treatment. Results The efficacy of cetirizine compared to that of loratadine was not statistically significant in diminishing nasal symptoms after 3 days, 7 days and 14 days of treatment (P=0.40, P=0.07, and P=0.057, respectively). Evaluation of side effects, however, revealed significantly fewer headaches in the cetirizine group after 3 days and 7 days of treatment (P=0.01 and P=0.03, respectively) than in the loratidine group. In addition, the loratadine group had significantly more instances of palpitations after 7 days of treatment (P=0.04) compared to the cetirizine group. Conclusion There was no significant difference in cetirizine and loratadine treatment effectiveness on allergic rhinitis. However, loratadine was found to cause more headaches and palpitations than cetirizine. [Paediatr lndones. 2012;52:61-6].